Synthesis of hydrazine‐fumaryl chloride‐based polyamide and its electrical conductivity studies. Issue 2 (5th January 2023) - Yadav, Shashikant; Tiwari, Rudramani; Verma, Dipendra Kumar; Kumar, Devendra; Adhikary, Pubali; Krishnamoorthi, Subramanian
Abstract: Perfect crisscross chain arrangements with high inter‐chain H‐bonding structure of conjugated polyamides are capable of inter‐chain proton transfer and this property of conjugated polyamides makes them semiconducting material. To establish this, we synthesized in situ HCl doped Hydrazine‐Fumaryl Polyamide (HFP) material via the condensation polymerization method. HFP was further modified by doping with Lewis acids BF3 and AlCl3 to increase the amorphous nature and ionic conductivity. Among the synthesized material, HFP–AlCl3 showed the highest amorphous property with the best bulk conductivity in the order of 10 −5  S/cm at room temperature. HFP and doped HFP showed correlated hopping type ( n  < 1) ionic dynamics in the polymer matrix. There was a high amount of charge associated with the polymer matrix (>10 6  F/m) with negligible electrode‐electrolyte effect contribution. These properties of materials can make them useful in the field of organic voltaic and fuel cell applications. Abstract : Equilibrium state in polymer backbone in self doped condition as well as doped with lewis acids.